Government Program In Addressing Stunting In Early Children In Kebonsari District, Jember District - Jasmine, Agvely Aulia; Pranoto, Yuli Kurniawati Sugiyo; Cahyati, Widya Harry (JURNAL PENDIDIKAN USIA DINI, 2025)
Basic Health Research data for 2018 revealed that Indonesia is ranked fifth and fourth highest in the world regarding wasting and stunting rates. The causes of stunting include limited access to nutritious food due to economic factors and knowledge. The purpose of writing this article is to understand the role of the government and analyze government programs in dealing with stunting in early childhood in Kebonsari Village, Jember Regency. The method used in this research is a qualitative method, using primary data from observations, interviews and documentation with Health Center midwives at the Kebonsari Village Health Center. There is secondary data from several research journals to find out what government programs are in dealing with stunting in early childhood in Kebonsari Village. This research focuses on government programs in handling stunting in Kebonsari Village, Jember Regency. The results of this research show that the government program in dealing with stunting in early childhood in Kebonsari Village is a concrete step taken by the government to overcome stunting in Kebonsari Village which is very concerned. In Kebonsari Village, we always carry out ongoing evaluations to study and find solutions to the stunting problem. The government carries out cross-sector coordination to carry out evaluations and follow-up by making direct contact with economically disadvantaged communities in fulfilling nutrition. The program is carried out by providing food assistance, as well as providing outreach regarding stunting prevention programs by conducting training courses, providing counseling, seminars, workshops and so on. Providing counseling on child rearing patterns at posyandu is also carried out to prevent the increase in stunting and to reduce stunting rates, providing milk for pregnant women from the Kebonsari Village Health Center. improving community nutrition through the supplementary food program at posyandu